Hubungan Peran Perawat sebagai Care Giver dengan Tingkat Depresi Penderita Kusta di Rumah Sakit Kusta Kota Kediri - Linda Ishariani; Didit Damayanti; Assa Tafrihatul Walidah (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
Leprosy including infectious, many people tend to ostracize leprosy patients causing depression in patients. Depression has a major influence on the decline in quality of life so that required management to overcome the role of nurses as care giver.Thisresearch aims to determine the relationship of nurse role as care giver with depression level of leprosy patients. The design of this researchwas descriptive correlation with cross sectional approach, with nurse population in the hospitalization service and all leprosy patients who were hospitalized in leprosy hospitalKediri city. The sample in this research obtained 24 nurse respondents and 24 respondents patients with total sampling technique, the instrument used nurse role observation sheet as care giver and depression level questionnaire analyzed by Spearman Rank test. The result of the research showed that the role of nurse as care giver of good criteria was (79,2%) and leprosy depression level in light category (62,5%). Spearman Rank statistic analysis shows that P-value <α (0,002 <0,05) there wasthe relationship of nurse role as care giver with leprosy depression level with medium relation level (-0,596), mean that the higher role of nurse as care giver, the more mild depression experienced by the patient. Nurses in leprosy hospitals should be able to assess the depression level as early as possible in order to detect early from depression, it was advisable for nurses to further enhance the role of care giver.